A Web-Based Credit Financing Eligibility Determination System for Multifinance Companies Using the Fuzzy Tsukamoto Method - Al Ihsan Fauzi Ardilla; Achmad Noe’man; Herlawati (Jurnal Kecerdasan Buatan dan Teknologi Informasi, 2026)
The credit eligibility analysis process in a financing company is a crucial stage in minimizing the risk of non-performing loans. However, the assessment process that still relies on the subjective interpretation of credit analysts potentially leads to inconsistencies in decision-making. This issue also occurs at PT Mandiri Utama Finance Bekasi Branch, which has shown a declining trend in financing performance based on the indicators of End Net Receivables (ENR), Total Over Due (TOD), and Net Credit Loss (NCL). This study aims to design and develop a web-based decision support system that can assist in determining credit financing eligibility by applying the Fuzzy Tsukamoto method based on the 5C principles (Character, Capacity, Capital, Collateral, and Condition). The research methods employed include observation, interviews, and literature studies. System development was carried out using the Waterfall model, comprising requirement analysis, system design, implementation, testing, deployment, and maintenance phases. The Fuzzy Tsukamoto method was utilized to process data containing uncertainty through fuzzification, IF-THEN rule-based inference, and defuzzification to generate credit eligibility scores. The expected result of this study is the creation of a web-based decision support system capable of providing credit eligibility recommendations that are more objective, consistent, and structured. Consequently, the developed system can assist credit analysts in the decision-making process and support the company’s efforts to minimize the risk of problematic financing.